2023
DOI: 10.5507/bp.2022.009
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nutritional support for patients undergoing elective colorectal cancer surgery - does it really work?

Abstract: Aims. This study aimed to evaluate the effect of preoperative administration of oral nutritional supplements (ONS) on the self-sufficiency, physical status, and nutritional status of patients undergoing elective colorectal resections. Methods. This prospective randomized clinical trial was conducted in a single institution. Patients scheduled to undergo colorectal cancer surgery were randomized to either ONS twice per day for 7 days before surgery or no ONS. Results. We enrolled 120 patients in the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…With such limited exposure, these interventions are less likely to demonstrate benefits on early postoperative outcomes. Our findings support that at least two weeks of surgical prehabilitation are necessary to expect an impact [ 28 , 29 , 30 , 32 , 38 ]. Unfortunately, in GI cancer resections, time is often considered of the essence to avoid disease progression, although this concept is challenged [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…With such limited exposure, these interventions are less likely to demonstrate benefits on early postoperative outcomes. Our findings support that at least two weeks of surgical prehabilitation are necessary to expect an impact [ 28 , 29 , 30 , 32 , 38 ]. Unfortunately, in GI cancer resections, time is often considered of the essence to avoid disease progression, although this concept is challenged [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
“…They did not find a significant difference in postoperative complications and 1-month hospital readmissions between groups. One study evaluated the effect of a 1-week high protein ONS supplementation on postoperative muscle mass and strength, complications, and LOS in patients with colorectal cancers [ 29 ]. They failed to demonstrate any difference between groups for all postoperative outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies examined preoperative use of immunonutrition, including use of oral immunonutrition in advanced pancreatic adenocarcinoma ( 31 ), enteral immunonutrition among patients with colorectal or gastric carcinoma ( 36 ), and immunonutrient-enriched supplementation in patients with colon cancer. Seven studies examined the use of more diverse oral nutrition support across gastrointestinal cancers, including use of preoperative Nutricia ( 35 ), hypercaloric supplementation (Nutridrink Protein) ( 28 ), peripheral intravenous nutrition for patients undergoing workup for biliopancreatic masses ( 29 ), oral nutrition combined with microbial preparations ( 33 ), preoperative oral supplementation for colorectal ( 34 ) and gastrointestinal cancers ( 27 ), and the use of Nutrison Fiber in patients with adenocarcinomas ( 37 ). The final 3 studies examined carbohydrate-rich beverages ( 26 , 32 ) as well as the use of 10% glucose solution before radical gastrectomy ( 25 ).…”
Section: Nutrition Interventions Before Cancer Treatmentmentioning
confidence: 99%
“…Among the 15 studies assessed for RoB ( Table 3 ), 8 were assessed as low or medium RoB and reported mixed results on development of complications, improvements in weight loss, and length of hospital stay ( Table 5 ) ( 23-25 , 27 , 30 , 32 , 34 , 36 ).…”
Section: Nutrition Interventions Before Cancer Treatmentmentioning
confidence: 99%